The concept of smart city and the perceptions of urban inhabitants: a case study from Žilina, Slovakia - Čorejová, Tatiana; Haľamová, Erika; Madleňák, Radovan; NeszmélyiGyörgy Iván (Hungarian Geographical Bulletin, 2021)
The smart city concept is a comprehensive approach to the functioning of the urban region. It concerns various areas of life such as culture, infrastructure, environment, energy, and social services. Public perceptions of the smart city concept are not commonly addressed. The aim of this paper is to examine perceptions of the smart city concept among inhabitants, doing so through a case study focusing on the city of Žilina in Slovakia. The methodology that the researchers applied includes primary research and surveys as well as secondary research. Based on the analysis of the environment and the results of the survey, opportunities for the development of a ‘Smart City Žilina’ concept are identified. There is a growing interest in green solutions among the inhabitants of Žilina. A significant number of respondents indicated their support for intelligent waste collection and renewable energy sources. And they were also supportive of green roofs. The update of the strategy must consider a number of steps in waste management, from collection to transport, with a view to the overall recovery of the waste generated. As part of the smart city concept and projects, the public administration and the municipality must communicate effectively with the public. This will require specific approaches and tactical decisions for optimal success.